Energetics of wave propagation leading to cold event in tropical latitudes of South America - Muller, Gabriela Viviana (2015)
This paper presents a new vision on the cold and cool events that affect the tropical region of South America, considering the dynamics and the energetics of wave train propagation associated with these systems. Through a composite analysis of meridional winds at 300 hPa for cold (T < 0 °C) and cool (0 °C ≤ T ≤ 2.5 °C) air incursions affecting tropical latitudes and causing frost are studied. The cold events observed in tropical latitudes are associated with a single Rossby wave pattern propagating over the Pacific Ocean which drives the low level anticyclone from the southwest of the continent to low latitudes. This propagation involves a southern circulation due to the meridional wind penetration and consequently cold air advection causing temperatures to drop below 0 °C. During cool events a subtropical wave train propagating through the Pacific Ocean is observed, which merges before the event with a wave coming from the subpolar latitudes of the South Atlantic Ocean. The zonal propagation leads to the entrance of the anticyclone from the west of the continent, and it is strengthened together with the meridionaly extended cyclone located upstream. This configuration causes southerly wind advection over central-southeastern Brazil and consequently causes the temperature decrease. The energetics shows that the cold events kinetic energy maxima are more intense than those of cool events. For the cold events three maxima are observed, the first (K1) and the third (K3) maxima are developed by baroclinic conversion and ageostrophic flux convergence and the second one (K2) by ageostrophic flux convergence. For the cool events two maxima are found, the first maximum (K4) developed by baroclinic conversion and the second one by ageostrophic flux convergence.